Table of contents, editorial board, and other front matter - Jean M. Rawson (Journal of Applied Communications, 1985)
Editorial front matter and table of contents for vol.68, no.3, July-Sept (1985) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education